Localisation Problems in Computer Games Translation - Abilkaiyr, А. (M. Narikbayev KAZGUU University School of Liberal Arts, 2023)
The computer gaming enterprises displayed themselves in their full splendour between the early 2000s and the middle of the 2010s; specifically, they exhibited not solely significant financial gain but also an influence on mankind in its entirety. For instance, if we consider the sociological and neurological disciplines, where research on the subject of video games started in the 1990s, there have been an immense number of scholarly publications from such disciplines have been published in recent years. Talking about the translation aspect, the global market for video games has made localisation among the most crucial elements in the marketing of the entirety of the video gaming industry. However, there has not been an adequate study done on the issue of localization, particularly when it comes to translating unique words and phrases used in video games. This study's objective is to deal with the issue in question. Written content from distinct genres of video games was examined in this study. The findings of which provided information on localisation mistakes and suggestions for avoiding them. This research will furthermore describe the localisation issues in detail and in addition, it also can be used as a guide that could assist in producing proficient video game localisations.
Keywords: video game localisation, culturally unique lexicon, video game, translational challenges